Acid Resistance Test of Probiotic Isolated from Silage Forage Swamp on In Vitro Digestive Tract - Sofia Sandi; Miksusanti Miksusanti; Meisji Liana Sari; Eli Sahara; Adi Supriyadi; Nuni Gofar; Asmak Asmak (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Antibiotics are commonly used in poultry ration, and afterward these drug residues may persist in foods. There is an alternative source of antibiotics in poultry rations, one of which is using probiotics. Probiotics are living microorganisms capable of reaching the gastrointestinal tract and benefiting health, leaving no residue in the body. Probiotics can be originated from bacteria such as lactic acid bacteria (LAB) which produced lactic acid and antimicrobial components. LAB must be able to live in the digestive system with various pH condition. pH resistance testing of LAB was performed by introducing diluted bacteria into several buffer solutions with different pH and a predetermined incubation time, then was grown in MRS agar medium. This study was conducted to determine the resistance of LAB isolates as probiotics from silage forage swamp at different pH distributed in vitro digestant. The design used was a complete randomized design consist of 3 treatments and 3 replications. The treatments were using isolate of Kumpai Tembaga silage (P1), isolate of 50% Kumpai Tembaga silage and 50% Kemon Air silage (P2), and isolate of Kemon Air silage (P3). The results showed that all isolates used were lactic acid bacteria, and the treatment significantly affected the value of LAB resistance test against low pH and high pH. Isolate from Kumpai Tembaga silage (P1) is a lactic acid bacterium with higher ability to survive in pH of in vitro digestive system.